ECONOMIC INSTRUMENTS FOR REDUCTION OF GREENHOUSE GAS EMISSION IN AGRICULTURE AND FORESTRY - Radmilo Pešić; Marko Ivaniš; Radivoj Prodanović (Ekonomika Poljoprivrede (1979), 2018)
A signifcant reduction of greenhouse gas emissions in agriculture and forestry can be achieved with adequate economic instruments. There are also other measures on disposal, such as good agricultural practice and organic production that involve the use of agronomic and biotechnological knowledge and skills with the purpose to produce healthy and safe food, with the preserving the environment and production resources. In the paper we analyze the previous experience in the application of economic instruments for the reduction of greenhouse effect in Agriculture and Forestry, in the broad and narrow sense, both in the domestic and international context. Special attention is given to the experiences in the implementation of the so-called flexibility mechanisms under the Kyoto Protocol. As a result of these experiences, in the period after 2012, new instruments have been created, mainly on a voluntary basis, which does not inspire confdence in their effectiveness. It has been noted that the system of economic instruments for the promotion of agricultural production in Serbia is in contradiction with the objectives of the climate protection policy. Changes are proposed in terms of abolishing direct benefts per hectare and the livestock units, as well as introduction of incentives for energy effciency, renewable energy sources, and specifcally for the organic production. Punitive measures must, once and for all, stop the harmful and dangerous practice of burning crop residues on felds.